Mutations of BRCA1, BRCA2, and PALB2 genes in breast tumor tissue: Relationship with the effectiveness of neoadjuvant chemotherapy and disease prognosis - Tsyganov, Matvey M.; Sorokovikova, Sofia S.; Lutzkaya, Elizaveta A.; Ibragimova, Marina K. (Genes)
It has been shown that the loss of function of the BRCA1, BRCA2, and PALB2 genes due to a number of hereditary mutations or chromosomal aberrations can affect the effectiveness of chemotherapy treatment and disease prognosis in patients with various types of cancer, and in particular in breast cancer. Thus, the aim of the work was to evaluate the predictive and prognostic potential of DNA copy number aberrations and mutations in the BRCA1, BRCA2, and PALB2 genes in breast tumors. Materials and Methods: The study included 66 patients with breast cancer. DNA copy number aberrations (CNA) were assessed by high-density CytoScanHD™ Array micro matrix analysis. Gene mutations were assessed by sequencing on the MiSeq™ Sequencing System using the Accel-Amplicon BRCA1, BRCA2, and PALB2 Panel. Results: It has been established that the presence of a normal copy number of PALB2 is associated with a lack of response to chemotherapy in Taxoterecontaining treatment regimens (p = 0.05). In addition, the presence of a PALB2 deletion is associated with 100% metastatic survival rates (log-rank test p = 0.04). As a result of sequencing, 25 mutations were found in the BRCA1 gene, 42 mutations in BRCA2, and 27 mutations in the PALB2 gene. The effect of mutations on the effectiveness of treatment is controversial, but an effect on the survival of patients with breast cancer has been shown. So, in the presence of pathogenic mutations in the BRCA2 gene, 100% metastatic survival is observed (log-rank test p = 0.05), as well as in the elimination of PALB2 mutations during treatment (log-rank test p = 0.07). Conclusion: Currently, there is little data on the effect of chromosomal aberrations and mutations in the BRCA1/2 and PALB2 genes on the effectiveness of treatment and prognosis of the disease. At the same time, the study of these genes has great potential for testing focused on a personalized approach to the treatment of patients with breast cancer.